Biodegradable Microspheres for Controlled Delivery of Metronidazole in the Treatment of Periodontal Diseases: Formulation Consideration - GAURAV TIWARI (International Journal of Pharma and Bio Sciences, 2010)
This study reports on the development of novel biodegradable microspheres prepared by oil-in-water–oil (O/W/O) double emulsion technique using the blends of poly (D, L-lactide-co-glycolide) (PLGA) and polycaprolactone (PCL) in different ratios for the controlled delivery of metronidazole (MTZ). Metronidazole encapsulation of up to 40% was achieved within the polymeric microspheres. Blend placebo microspheres, drug-loaded microspheres were analyzed by Fourier transform infrared spectroscopy (FT-IR), which indicated no interaction between drug and polymers. Differential scanning calorimetry (DSC) on drug-loaded microspheres confirmed the polymorphism of MTZ and indicated a molecular level dispersion of MTZ in the microspheres. Scanning electron microscopy (SEM) confirmed the spherical nature and smooth surfaces of the microspheres produced. Mean particle size of the microspheres as measured by dynamic laser light scattering method ranged between 100 and 200 µm. In vitro release studies performed in 7.4 pH media indicated the release of MTZ from 7 to 11 days, depending upon the blend ratio of the matrix. Up to 11 days, MTZ concentrations in the gingival crevicular fluid were higher than the minimum inhibitory concentration of MTZ against most of the periodontal pathogens. Statistical analyses of the release data were performed using the analysis of variance (ANOVA) method.